Physico-enzymatic characteristics of cervical mucus with reference to fertility in repeat breeder cows - SELVARAJU, P; KUMAR, HARENDRA; MAHMOOD, S (The Indian Journal of Animal Reproduction, 2023)
The higher occurrence of turbid CM and atypical fem pattern was observed in RB cows. Both ACP and AKP inestrual CM were significantly (P
Keywords: Cervical mucus; fem pattern; ACP; AKP; fertility; repeat breeder cattle